Neural gliding and neural tensioning differently impact flexibility, heat and pressure pain thresholds in asymptomatic subjects: A randomized, parallel and double-blind study. (March 2019) - Martins, Carolina; Pereira, Rebeca; Fernandes, Inês; Martins, Joana; Lopes, Tiago; Ramos, Luis; Pacheco, Joana; Silva, Anabela G.
Abstract: Objective: To compare the effect of neural gliding and tensioning on hamstring flexibility, nerve function (heat and cold thresholds) and pain sensitivity (pain intensity and pressure pain threshold) of the mobilized and non-mobilized lower limbs at post-intervention and 24 h follow up. Design: Randomized, parallel and double blinded trial. Setting/participants: Forty-eight asymptomatic participants. Intervention(s): Participants received neural gliding (n = 23) or tensioning (n = 25). Main Outcome Measures – Straight leg raising (SLR; in degrees), heat and cold threshold (ºC), pressure pain threshold (PPT; in Kgf) and pain intensity (visual analogue scale), taken at baseline, post-intervention and at 24 h follow up. Results: There was a significant interaction between time, intervention and limb for SLR (F2, 45 = 3.83; p = 0.029). A significant interaction between time and intervention for PPT (F2, 45 = 3.59; p = 0.036) and heat threshold (F2, 45 = 5.10; p = 0.01). A significant effect of time (F2, 45 = 9.42; p < 0.001) and of limb (F1, 46 = 4.78; p = 0.035) for pain intensity during SLR, and a significant effect of time (F2, 45 = 3.65; p = 0.034) for pain intensity during PPT. Conclusion: Gliding and tensioning had similar and positive effects for flexibility in the mobilized limb, but tensioning was superior for the non-mobilized limb. Gliding was superior to tensioning for pressure pain and heat thresholds. Highlights: Neural gliding and tensioning impact both the mobilized and the non-mobilized limb. Neural gliding is superior to tensioning for hypoalgesia to mechanical pressure and heat threshold. Neural gliding and tensioning impact perceived pain intensity to stretching and pressure. Neural gliding and tensioning improve flexibility, but tensioning is superior for the contralateral limb.